Biochemical characterization of a novel beta-1-3, 1-4 glucan 4-glucanohydrolase from thermomonospora sp having a single active site for lichenan and xylan - Anish, Ramakrishnan; Rao, Mala (Biochimie, 2007)
A bifunctional high molecular weight (Mr, 64,500 Da) beta-1-3, 1-4 glucan 4-glucanohydrolase was purified to homogeneity from Thermomonospora sp., exhibiting activity towards lichenan and xylan. A kinetic method was used to analyze the active site that hydrolyzes lichenan and xylan. The experimental data was in agreement with the theoretical values calculated for a single active site. Probing the conformation and microenvironment at active site of the enzyme by fluorescent chemo-affinity label, OPTA resulted in the formation of an isoindole derivative with complete inactivation of the enzyme to hydrolyse both lichenan and xylan confirmed the results of kinetic method. OPTA forms an isoindole derivative by cross-linking the proximal thiol and amino groups. The modification of cysteine and lysine residues by DTNB and TNBS respectively abolished the ability of the enzyme to form an isoindole derivative with OPTA, indicating the participation of cysteine and lysine in the formation of isoindole complex. (C) 2007 Elsevier Masson SAS. All rights reserved.
Keywords: 1-4 glucan 4-glucanohydrolase; beta-1-3; bifunctional; O-phthaialdehyde; single active site; Thermomonospora sp.; Xylanase